Integrating Technology and Pedagogy: The Development of an Rme-Based Interactive Website For Re-Contextualizing Number Concept - Nugraha, Aditiya Eka; Lestiana, Herani Tri (Educational Insights, 2025)
The present study aims to design and develop an interactive website as a learning medium grounded in the Realistic Mathematics Education (RME) approach, specifically focusing on number concepts for seventh-grade junior high school students. This research employed the Research and Development (R&D) methodology utilizing the ADDIE model, encompassing five systematic phases: Analysis, Design, Development, Implementation, and Evaluation. The validation process involved five experts consisting of mathematics education lecturers and teachers. The validation outcomes demonstrated that the developed media met the feasibility criteria and was categorized as "good" in the aspects of content, media, and language. A limited implementation involving 20 students revealed highly positive responses, indicating that the website was both practical and engaging, with an average score exceeding 85%. The developed website facilitates contextualized learning of number concepts, enhances interactivity, and promotes students' engagement and conceptual understanding. Thus, the interactive website is deemed appropriate to serve as a digital alternative instructional medium in mathematics education.